Frequency of Syndrome of Inappropriate Antidiuretic Hormone in Patients with Guillain-Barré Syndrome Presenting at Tertiary Care Hospital, Karachi: Antidiuretic Hormone in Guillain-Barré Syndrome Patients - Kumari, Monika; Ali, Syed Gohar; Hyder, Fezan; Das, Teerth; Syed, Mohsina; Abbasi, Irfana (Pakistan Journal of Health Sciences, 2025)
Guillain-Barré Syndrome (GBS) is a condition that causes inflammation in the nerves and can sometimes lead to a problem called SIADH. SIADH happens when the body makes too much of a hormone that controls water balance, leading to low sodium levels in the blood. Objective: To determine the frequency of SIADH inpatients with GBS presenting at Tertiary Care Hospital, Karachi. Methods: This Cross-sectional study was conducted at Department of Neurology, Civil Hospital, Karachi, from 12-07-19 till 12-01-20. Total 119 GBS patients who met the inclusion criteria were included. A brief history was recorded, and demographic details were noted in the form. Numerical data were summarized using simple descriptive statistics. Categorical data were shown as numbers and percentages. Results: 71 (59.7%) were male and 48 (40.3%) were female. Mean age in the study was 46.78 ± 2.81 years. Whereas, Mean age, duration of symptoms, serum sodium and GC Sinour study was 46.78 ± 2.81 years, 25 ± 10.78 hours, 128.65 ± 7.52 mmol/L and 11.21 ± 3.14 % respectively. Out of 119 GBS patients, 21% had SIADH. Conclusions: This study showed that SIADH is present in significant proportion of patients with GBS. Thus, it is essential to focus on a comprehensive way of management of GBS and its comorbidities rather than primarily treating the neurological symptoms.